2021
DOI: 10.1016/j.geomorph.2021.107925
|View full text |Cite
|
Sign up to set email alerts
|

Inverted channel variations identified on a distal portion of a bajada in the central Atacama Desert, Chile

Abstract: In deserts, the interplay between occasional fluvial events and persistent aeolian erosion can form composite modern and relict surfaces, especially on the distal portion of alluvial fans. There, relief inversion of alluvial deposits by differential erosion can form longitudinal ridges. We identified two distinct ridge types formed by relief inversion on converging alluvial fans in the hyperarid Chilean Atacama Desert. Although they are co-located and similar in scale, the ridge types have different ages and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 125 publications
(205 reference statements)
1
6
0
Order By: Relevance
“…Moreover, when comparing the rivers with nearly similar discharge from different fluvial depositions environments, our drainage areas are close to those formed under flashier climates (Figure 8). A similar paleoenvironmental interpretation has been observed from fluvial ridge systems in the Kumtagh Desert, China (Wang et al, 2015), Ad Dwasir, Saudi Arabia (Matter et al, 2016), and the Atacama Desert (e.g., Morgan et al, 2014;Williams et al, 2021), where coarse materials from local bedrock sources are prevalent and were deposited over short durations, that is, thousands to tens of thousands years. Hayden, Lamb, and McElroy (2021) calculated the median of intermittency of the gravel-bed river at 0.092, which means that the formative fluvial events could occur over a few days to several weeks every year, which could be applied to the ancient gravel-bed rivers investigated here.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, when comparing the rivers with nearly similar discharge from different fluvial depositions environments, our drainage areas are close to those formed under flashier climates (Figure 8). A similar paleoenvironmental interpretation has been observed from fluvial ridge systems in the Kumtagh Desert, China (Wang et al, 2015), Ad Dwasir, Saudi Arabia (Matter et al, 2016), and the Atacama Desert (e.g., Morgan et al, 2014;Williams et al, 2021), where coarse materials from local bedrock sources are prevalent and were deposited over short durations, that is, thousands to tens of thousands years. Hayden, Lamb, and McElroy (2021) calculated the median of intermittency of the gravel-bed river at 0.092, which means that the formative fluvial events could occur over a few days to several weeks every year, which could be applied to the ancient gravel-bed rivers investigated here.…”
Section: Discussionsupporting
confidence: 65%
“…Hayden et al (2019) suggested that ridges recording long-lived fluvial activity that persisted over millions of years may favor habitability on early Mars. However, Williams et al (2021) reported fluvial ridges from the Atacama Desert, Chile, preserving potential biosignatures, including plants and subsurface organisms over short durations, that is, thousands of years. This study also indicates that fluvial landforms deposited by short-duration fluvial activity (10-100s years over thousands of years) also supported habitable environments for biosignature, including bacterial structures and organisms in the eastern Sahara (e.g., Cremaschi et al, 2010;Nicoll & Sallam, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capped duricrust are known to have a protective effect, resistant enough to preserve ancient landscapes 15 , 35 . The observation of sulphate-capped ridges from the Atacama Desert, resembling inverted fluvial stream channel indicate that sulphate cementation is able to increase the erosion resistance against fluvial and aeolian processes 57 . Studies of gypcrete in Egypt 36 supports the protective nature of gypsum crusts against erosion and weathering, consolidating surface layers by cementation.…”
Section: Caso 4 -Rich Soil As Landscape Forming Agentmentioning
confidence: 96%
“…the evolution of duricrusts, might have relevance to other arid to hyperarid climates and for the geomorphology of Mars, where similar channel forms are evident 45 – 48 , 50 – 53 . The Atacama Desert serves as a natural laboratory for potential surface processes on Mars due to the broadly similar climatic conditions and geochemical/mineralogical compositions 32 , 57 , 59 . Sulphates (albeit MgSO 4 60 ) are abundant on Martian surface 60 66 and atmospheric deposition of sulphates from volcanic origin 67 , 68 may give rise to surface encrustations that are similar to those found in the Atacama 9 – 11 , 27 .…”
Section: Caso 4 -Rich Soil As Landscape Forming Agentmentioning
confidence: 99%